Enhancing the Transient State Performance of Permanent Magnet Synchronous Generator Based Variable Speed Wind Turbines Using Power Converters Excitation Parameters - Okedu, Kenneth E.; Barghash, Hind (Frontiers in Energy Research, 2021)
One of the ways of generating electrical power from wind energy is by employing the promising technology of the permanent magnet synchronous generator (PMSG) variable speed wind turbine (VSWT). With the daily increase and integration of wind farms into traditional power grids, it is imperative to carry out transient stability studies of wind generators in wind farms, in order to fulfill the operational grid codes. To solve the transient stability intricacies posed by the stochastic nature of wind energy during transient states or grid faults, this paper presents the enhancement of PMSG wind turbine considering the excitation parameters of the insulated gate bipolar transistors (IGBTs) of the wind generator. The investigation was carried out using the turn on and turn off resistances of the IGBTs of the power converters of the PMSG wind turbine, considering different scenarios, with and without over voltage protection scheme. A severe three-line-to-ground fault was used to test the robustness and rigidity of the controllers of the wind generator during transient state. Furthermore, the results obtained using the PMSG wind turbine were compared to those using the doubly fed induction generator (DFIG) wind turbine. The evaluation of the system performance was done using the power system computer “aided” design and electromagnetic transient including DC (PSCAD/EMTDC) platform. The same conditions of operation were used in investigating the various scenarios considered in this study.